2009
DOI: 10.1158/0008-5472.sabcs-5117
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of a 3-weekly liposome-encapsulated doxorubicin/docetaxel/pegfligrastrim in combination with weekly trastuzumab as primary treatment in HER2 positive early stage breast cancer patients (II-IIIa). GEICAM 2003-03 study.

Abstract: #5117 Objective: To assess the safety and efficacy of Myocet (M), Docetaxel (T), Trastuzumab (H) with prophylactic Pegfilgrastrim (N) as neoadjuvant chemotherapy in operable breast cancer patients (pts). The primary efficacy end point was pathologic complete response in the breast. Methods: Eligible pts had pathologically confirmed stage II or IIIA untreated breast cancer and HER2 overexpression determined by FISH in a central laboratory. M 50 mg/m2 and T 60 mg/m2 were given on day 1 and N on da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In addition, substituting NPLD for conventional doxorubicin as the standard anthracycline in early breast cancer (EBC) may help address the growing concerns regarding the longer-term impact of treatment on cardiac function [ 1 , 2 ]. Current evidence on the use of NPLD in early disease is restricted to two phase II trials [ 8 , 9 ], both of which report limited cardiac data for NPLD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, substituting NPLD for conventional doxorubicin as the standard anthracycline in early breast cancer (EBC) may help address the growing concerns regarding the longer-term impact of treatment on cardiac function [ 1 , 2 ]. Current evidence on the use of NPLD in early disease is restricted to two phase II trials [ 8 , 9 ], both of which report limited cardiac data for NPLD.…”
Section: Discussionmentioning
confidence: 99%
“…The results of two small phase II studies [8, 9] suggest that the benefits observed in metastatic patients may be maintained in early breast cancer, but further data are required. The objective of our study, therefore, was to assess the use of NPLD in place of conventional doxorubicin in standard regimens as a novel therapeutic option for the treatment of patients with early breast cancer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations